2007
DOI: 10.1128/aac.00647-07
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Combined Effects of Topoisomerase Mutations toward Fluoroquinolone Resistance in Escherichia coli

Abstract: In defined, isogenic strains, at least three mutations, two of which must be in gyrA, were required to exceed the CLSI breakpoint for fluoroquinolone resistance. Strains with double mutations in both gyrA and parC had even higher MICs of fluoroquinolones than strains with totals of three mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…The expression of qnr genes in the E. coli ATCC-Ser83Leu strain gave a less marked increase, with CIP MICs of 0.5, 0.5, and 1 g/ml, meaning 4-, 4-, and 8-fold increases in expression for qnrA1, qnrB1, and qnrS1, respectively. The Ser80Arg substitution in ParC played a secondary role in FQ resistance (Table 1), as previously described (7,12). In E. coli ATCC-Ser83Leu-Ser80Arg, the presence and expression of qnrA1 or qnrS1 genes increased the CIP MIC to 2 g/ml (or intermediate susceptibility according to CLSI guidelines) (Table 1) (2).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The expression of qnr genes in the E. coli ATCC-Ser83Leu strain gave a less marked increase, with CIP MICs of 0.5, 0.5, and 1 g/ml, meaning 4-, 4-, and 8-fold increases in expression for qnrA1, qnrB1, and qnrS1, respectively. The Ser80Arg substitution in ParC played a secondary role in FQ resistance (Table 1), as previously described (7,12). In E. coli ATCC-Ser83Leu-Ser80Arg, the presence and expression of qnrA1 or qnrS1 genes increased the CIP MIC to 2 g/ml (or intermediate susceptibility according to CLSI guidelines) (Table 1) (2).…”
mentioning
confidence: 78%
“…In a recent study (12), the combined effect of topoisomerase mutations on FQ resistance in isogenic Escherichia coli strains showed that at least three mutations-two of which had to be in gyrA-were necessary to exceed CLSI resistance breakpoints. Plasmid-mediated quinolone resistance (PMQR) genes confer low levels of quinolone resistance, and their precise effect on selecting for quinolone resistance in association with other mechanisms is not well known.…”
mentioning
confidence: 99%
“…As presented in the introduction, MICs for strains containing multiple mutations in the topoisomerase genes are ϳ10-fold higher for ciprofloxacin and norfloxacin than gatifloxacin and levofloxacin (17). In addition, ciprofloxacin and norfloxacin, but not gatifloxacin or levofloxacin, are substrates of the plasmid-encoded acetyltransferase Aac(6Ј)-Ib-cr (16) and efflux pump QepA (21,27).…”
Section: Discussionmentioning
confidence: 99%
“…The fluoroquinolones, however, vary with regard to pharmacokinetic and pharmacodynamic parameters, including potency (reviewed in reference 24). Additionally, data from defined, isogenic strains of Escherichia coli have shown that fluoroquinolone resistance genotypes can affect the MICs of various fluoroquinolones differently (17,26,28). For example, regimens of ciprofloxacin (100, 250, 500, or 750 mg twice daily), moxifloxacin (400 mg once daily), and norfloxacin (200 mg twice daily) differ in their ability to eradicate E. coli singlemutant (one mutation in the gyrA gene of gyrase) and doublemutant (mutations in both gyrA and marR, which encodes a repressor of the multidrug efflux pump AcrAB) strains in vitro; only 750 mg of ciprofloxacin dosed twice daily eliminated both strains (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation